Characteristics of alveolar macrophages from murine models of OVA-induced allergic airway inflammation and LPS-induced acute airway inflammation. (9th August 2015) - Katsura, Yoko; Harada, Norihiro; Harada, Sonoko; Ishimori, Ayako; Makino, Fumihiko; Ito, Jun; Kamachi, Fumitaka; Okumura, Ko; Akiba, Hisaya; Atsuta, Ryo; Takahashi, Kazuhisa
ABSTRACT: Background : Macrophages include the classically activated pro-inflammatory M1 macrophages (M1s) and alternatively activated anti-inflammatory M2 macrophages (M2s). The M1s are activated by both interferon-γ and Toll-like receptor ligands, including lipopolysaccharide (LPS), and have potent pro-inflammatory activity. In contrast, Th2 cytokines activate the M2s, which are involved in the immune response to parasites, promotion of tissue remodeling, and immune regulatory functions. Although alveolar macrophages (AMs) play an essential role in the pulmonary immune system, little is known about their phenotypes. Methods : Quantitative reverse transcription polymerase chain reaction and flow cytometry were used to define the characteristics of alveolar macrophages derived from untreated naïve mice and from murine models of both ovalbumin (OVA)-induced allergic airway inflammation and LPS-induced acute airway inflammation. AMs were co-cultured with CD4 + T cells and were pulsed with tritiated thymidine to assess proliferative responses. Results : We characterized in detail murine AMs and found that these cells were not completely consistent with the current M1 versus M2-polarization model. OVA-induced allergic and LPS-induced acute airway inflammation promoted the polarization of AMs towards the current M2-skewed and M1-skewed phenotypes, respectively. Moreover, our data also show that CD11c + CD11b + AMs from the LPS-treated mice play a regulatory role in antigen-specific T-cell proliferation in vitro. Conclusions : These characteristics of AMs depend on the incoming pathogens they encounter and on the phase of inflammation and do not correspond to the current M1 versus M2-polarization model. These findings may facilitate an understanding of their contributions to the pulmonary immune system in airway inflammation.